A single dose of hydrocortisone does not alter interhemispheric transfer of information or transcallosal integration - Berretz, Gesa; Packheiser, Julian; Wolf, Oliver T.; Ocklenburg, Sebastian (Frontiers in Psychiatry, 2023)
Stress has been suggested as a factor that may explain the link between altered functional lateralization and psychopathology. Modulation of the function of the corpus callosum via stress hormones may be crucial in this regard. Interestingly, there is evidence that interhemispheric integration and hemispheric asymmetries are modifiable by endocrinological influences. In previous studies, our group could show an enhancing effect of acute stress on interhemispheric integration. To investigate if this effect can be attributed to an increase in the stress hormone cortisol, 50 male participants received 20mg hydrocortisone or a placebo in a double-blind crossover design. In each test session, we collected EEG data while participants completed a lexical decision task and a Poffenberger paradigm. In the lexical decision task, we found shorter latencies of the N1 ERP component for contralateral compared to ipsilateral presentation of lexical stimuli. Similarly, we replicated the classical Poffenberger effect with shorter ERP latencies for stimuli presented in the contralateral visual field compared to the ipsilateral visual field. However, no effect of cortisol on latency differences between hemispheres could be detected. These results suggest that a temporary increase in cortisol alone might not be enough to affect the interhemispheric transfer of information via the corpus callosum. Together with previous results from our group, this suggests that chronically elevated stress hormone levels play a more central role in the relationship between altered hemispheric asymmetries and a variety of mental disorders.